Modelling water scarcity and water footprint of agricultural crops: A case from a semi-arid region in Morocco - Oumaima Attar; Marianna Leone; Anna Maria De Girolamo; Lhoussaine Bouchaou; Youssef Brouziyne; El Mahdi El Khalki; Hamza Berrouch; Soufiane Taia; Mohammed Hssaisoune; Yassine Ait Brahim (Journal of Hydrology: Regional Studies)
Study region: The Iguidi watershed is located in southeastern Morocco and represents semi-arid region where limited water resources constrain agricultural productivity and sustainability. Study focus: This study assesses the water footprint (WF) of four major crops: walnuts, wheat, olives, and almonds cultivated in the Iguidi watershed between 1992 and 2021. The Soil and Water Assessment Tool Plus (SWAT+) was used to simulate hydrological processes and estimate crop WF, including green and blue water components. The model was calibrated and validated using observed streamflow, with satisfactory performance (calibration: r = 0.80, R² = 0.55, NSE = 0.55; validation: r = 0.84, R² = 0.55, NSE = 0.55). Plant growth parameters were manually adjusted to improve crop model performance. New hydrological insights for the region: Results indicate significant differences in crop water use, with olives showing the highest total WF (2704.8 m³/t) and wheat the lowest (1482.86 m³/t). Blue Water Scarcity (BWS) increased sharply after 2017, with the index increasing from an average of 0.5 (1995–2021) to 2.4 in 2019. Green Water Scarcity (GWS) also increased after 2017, following a relatively stable period between 2009 and 2017 (average = 0.42). These findings indicate intensifying water stress in the watershed and underscore the need for adaptive and integrated water management strategies to enhance agricultural resilience in semi-arid regions.